Indios Kayapo - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observó a una mamá del grupo etnico Kayapo pintando con colores naturales provenientes de vegetales de color negro a su pequeño hijo conocido con el nombre de "Cenipapo" cuya mescla vegetal y polvo de carbon molido con una duracion aproximado de 10 dias y la mama repetira este proceso cada 15 dias en una forma de educar asu pequeño hijo
ENGLISH: A mother from the Kayapo ethnic group was observed painting her little son known by the name of "Cenipapo" with natural colors from black vegetables, whose vegetable mixture and ground charcoal powder lasted approximately 10 days and the mother would repeat This process every 15 days is a way to educate your little son.

SPANISH: Se observó a una mamá del grupo etnico Kayapo pintando con colores naturales provenientes de vegetales de color negro a su pequeño hijo conocido con el nombre de "Cenipapo" cuya mescla vegetal y polvo de carbon molido con una duracion aproximado de 10 dias y la mama repetira este proceso cada 15 dias en una forma de educar asu pequeño hijo
ENGLISH: A mother from the Kayapo ethnic group was observed painting her little son known by the name of "Cenipapo" with natural colors from black vegetables, whose vegetable mixture and ground charcoal powder lasted approximately 10 days and the mother would repeat This process every 15 days is a way to educate your little son.
Kayapo Indians
Keywords: Mato Grosso (Brasil)--Indigenous Community|~|Brazil--Indigenous populations|~|Mato Grosso (Brasil)|~|Comunidad Indigena|~|Brasil|~|Poblaciones Indigenas|~|Mato Grosso (Brazil)|~|Indigenous Community|~|Brazil|~|Indigenous Populations